Las actividades físicas recreativas para el buen vivir del adulto del barrio Pichik, parroquia San Lucas, cantón Loja - Condolo Puchaicela, Ángel Samael (2016)
The present thesis refers to: THE RECREATIONAL PHYSICAL ACTIVITIES FOR THE GOOD LIFE FOR THE ADULT OF THE PICHICK, NEIGHBORHOOD SAN LUCAS, PARISH, LOJA CANTON. The central problem defined as: the lack of physical activities program does not provides a good life for the adults of the Pichick neighborhood, San Lucas parish, Loja canton. As a general objective: Determine if the recreational physical program of the recreational physical activities improve the quality of life of the adults of the Pichick neighborhood, San Lucas parish, Loja canton. The methods used for the development of the present research work were: the scientific, inductive-deductive, analytic-synthetic, historical logic and the statistics model. The same were used as a support to achieve the efficiency of the proposed goal. The following techniques and instruments used were: survey for the adults regarding the attitudes in the practice of the physical activity, an observation guide to monitor the development of the physical activities of the adults in the neighborhood, and a test of physical efficiency to know the current status of the adult of the Pichick, neighborhood, San Lucas. The same techniques provided the results of the initial diagnosis and will facilitate all the processes of the research. Through these results the alternative proposal will be applied and then the post-test will be developed which will evaluate this alternative.